2015
DOI: 10.11604/pamj.2015.22.7.7474
|View full text |Cite
|
Sign up to set email alerts
|

Hernie inguinale de la vessie: à propos de 8 cas

Abstract: Décrire notre expérience de la prise en charge des hernies inguinales de la vessie (HIV). Il s'agit d'une étude rétrospective descriptive colligeant les dossiers des patients opérés pour une HIV entre janvier 2005 et décembre 2012. Les paramètres suivants ont été étudiés: l’âge des patients, les aspects anatomo-cliniques de la hernie, les circonstances de découverte, l'attitude thérapeutique et les résultats de la cure. Huit HIV ont été diagnostiquées sur une période de 7 ans. Tous les patients étaient de sexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In New York, Wantz [5] reported 2 cases of testicular atrophy out of 1682 Shouldice-type herniorraphies for primary hernia and 5 cases of testicular atrophy out of 311 herniorraphies for recurrence. In Senegal, Sarr et al [6] reported 6 cases of accidental opening of the bladder in intraoperative, a case diagnosed in immediate postoperative by a urine outlet through the surgical wound. In Guinea, the lack of previous studies on the subject and the clinical psycho-social severity related to some of these complications was the aim of this study.…”
Section: It Is At the Origin Of Approximately 120000 Surgical Interve...mentioning
confidence: 99%
“…In New York, Wantz [5] reported 2 cases of testicular atrophy out of 1682 Shouldice-type herniorraphies for primary hernia and 5 cases of testicular atrophy out of 311 herniorraphies for recurrence. In Senegal, Sarr et al [6] reported 6 cases of accidental opening of the bladder in intraoperative, a case diagnosed in immediate postoperative by a urine outlet through the surgical wound. In Guinea, the lack of previous studies on the subject and the clinical psycho-social severity related to some of these complications was the aim of this study.…”
Section: It Is At the Origin Of Approximately 120000 Surgical Interve...mentioning
confidence: 99%